Steam Package Boiler Expert System for Control and Maintenance of Fertilizer Plants using Rule-Base Fuzzy Logic (Global Journal of Computer Science and Technology, 2022)
Generally, expert systems have been found very useful and even in fertilizer plants it has been deployed in handling operations in critical sections, such as material handling systems, online detection systems, granulation, air compressor among others. This paper presents research work for steam package boiler expert system for control and maintenance of fertilizer plants using rule-base fuzzy logic hybrid system, which has not been benefited much from expert system. The system handles cause of boiler failures in terms of controlling and maintaining the functional chemical components of the boiler drum and feed water parameters. validation on the system consistency, correctness, and its precision with six (6) steam package boiler parameters test value cases was conducted involving fourteen (14) fertilizer plant boiler domain partitioners. The boiler drum and feed water qualities with less or higher test value worst-cases validates the boiler system, showing each of the parameters bar turns red, as displayed on the boilers panel, while on test value best-cases, validates the system, displaying green on the boilers panel bar as users entered the right value of parameters as design specification. The expert system prevents damaged and malfunctioning as control the alkalinity, prevent scaling, both mechanical
Keywords: expert system; rule-base system; fuzzy logic; steam package boilers; dynamic simulation